The errant king - Batson, Wayne Thomas (Chattanooga, Tennessee : Living Ink Books, 2011)
"Deep in the caves of the distant Hinderlands, an ancient menace stirs. Townsfolk shudder at violent memories of The Red Queen and even dare to whisper the name Raudrim. At the same time, word comes to Alastair that Cythraul has at last resurfaced, seeking a devastating weapon in the ruins of Grayvalon. Blood-soaked clues lead Alastair into a confrontation from which only one warrior will return alive. Meanwhile in Anglinore, young Lochlan Stormgarden, the new High King of Myriad, leaves the pomp and politics of the throne once too often. While blending in with the people of his kingdom, Loch suddenly realizes that he's put them all at risk. The fate of his new found love Arianna, his best friend Telwyn, his family, and indeed the world of Myriad all depend on the decisions of the errant king."--Back cover
Keywords: Good and evil -- Fiction; Magic -- Fiction; Fantasy fiction